Exploring the adoption and implementation of sustainable business practices policy in Sabah - Mohamad Isa Abd Jalil; Suddin Lada; Siti Hajar Samsu; Izaan Azyan Abdul Jamil; Rudy Ansar (Penerbit Universiti Malaysia Sabah, 2024)
This study explores the adoption and implementation of sustainable business practices in Sabah, Malaysia, in the context of the Sabah Maju Jaya (SMJ) Plan 1.0 (2021-2025) and the broader goals of sustainable development. The research develops a policy framework tailored to Sabah's unique environment, emphasizing the integration of environmental stewardship, economic growth, and social equity. By reviewing existing policies and comparing them with successful international frameworks, the study identifies gaps and opportunities for enhancing sustainability in Sabah's business sector. The findings highlight the importance of collaboration between government, industry, and local communities in overcoming economic, technological, cultural, and behavioral challenges. The proposed framework aims to foster a balanced approach to development that preserves natural resources while promoting economic resilience and social well-being. The study concludes with recommendations for strengthening Sabah's policy framework to support and reward sustainable business practices, ensuring long-term environmental and economic benefits for the state.